Students' Misconceptions in Solving Problems Based on the Newman Procedure Seen from Mathematical Disposition - Nur Hidayah; Amanda Syahri Nasution (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2024)
The aim of this research is to determine the factors and the influence of conceptual errors in solving problems in the form of story problems based on newman procedures in terms of mathematical disposition. This research uses a mixed method. The population of this study were seventh-grade students of MTs LAB Al Washliyah Medan with a total of 133 students. The sample was selected by purposive sampling, 30 students for quantitative data and 3 students for qualitative data. Qualitative data analysis methods involve the process of reducing, conveying and verifying data. Meanwhile, quantitative data uses hypothesis testing stages using factor analysis tests, simple linear regression and F tests. The results of qualitative data research show that conceptual errors in solving problems in the form of story problems based on Newman procedures are in line with the criteria for students' mathematical disposition. Quantitative data shows that there is only one factor formed and there is a significant influence between mathematical disposition and concept errors in solving story problems based on newman.